2008
DOI: 10.1007/s10722-008-9373-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of HMW glutenin subunits in diploid, tetraploid and hexaploid Triticum species

Abstract: The genetic variations of high-molecularweight (HMW) glutenin subunits in 1051 accessions of 13 Triticum subspecies were investigated using sodium dodecyl sulfate polyacrylamide-gel electrophoresis. A total of 37 alleles were detected, resulting in 117 different allele combinations, among which 20, 68 and 29 combinations were observed in diploid, tetraploid and hexaploid wheats, respectively. Abundance and frequency of allele and combinations in tetraploid wheats were higher than these in hexaploid wheats. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 57 publications
2
25
3
3
Order By: Relevance
“…Besides in the diploid T. urartu, T. boeoticum and T. monococcum (Ciaffi et al 1998;Ma et al 2007;Hu et al 2008), and the tetraploid T. dicoccoides Ciaffi et al 1993), T. carthlicum Nevski (Xu et al 2009), T. durum (Ciaffi et al 1991), T. dicoccon (Jiang et al 2009) and T. timopheevii Zhuk. (Wan et al 2002), the present study found that 1Ay subunit also existed in the tetraploids T. turgidum, T. polonicum and T. turanicum, and in the hexaploid T. zhukovskyi (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides in the diploid T. urartu, T. boeoticum and T. monococcum (Ciaffi et al 1998;Ma et al 2007;Hu et al 2008), and the tetraploid T. dicoccoides Ciaffi et al 1993), T. carthlicum Nevski (Xu et al 2009), T. durum (Ciaffi et al 1991), T. dicoccon (Jiang et al 2009) and T. timopheevii Zhuk. (Wan et al 2002), the present study found that 1Ay subunit also existed in the tetraploids T. turgidum, T. polonicum and T. turanicum, and in the hexaploid T. zhukovskyi (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The 1Ay subunit encoded by the y-type gene at Glu-1A locus has been deemed to be always silent in hexaploid wheat (Forde et al 1985;Halford et al 1989) with the exception of two Swedish bread wheat lines (Margiotta et al 1996). However, 1Ay subunit can express in some wild diploid (AA, 2n = 2x = 14) (Ciaffi et al 1998;Ma et al 2007;Hu et al 2008) and tetraploid wheat lines (AABB, 2n = 4x = 28) Ciaffi et al 1991;Ciaffi et al 1993;Wan et al 2002;Jiang et al 2009;Xu et al 2009). Some durum lines containing 1Ay subunit transferred from T. dicoccoides Körn.…”
Section: Introductionmentioning
confidence: 99%
“…The Glu-A1 locus consists of two tightly linked genes that encode one larger x-type and one smaller y-type subunit, i.e., Glu-A1x and Glu-A1y. The 1Ay subunit is absent from common wheat because of gene silencing (Forde et al 1985;D'Ovidio et al 1996;Xu et al 2009;Hu et al 2012). However, the 1Ay subunit is expressed in wild relatives of wheat, such as T. urartu, T. monococcum ssp.…”
Section: Discussionmentioning
confidence: 99%
“…monococcum has high protein content and disease resistance for cultivated polyploid wheats (Lawrence et al 1958;Fedak 1985;Tranquilli et al 2002;Zaharieva and Monneveux 2014). Although the variability of the seed storage protein in this species has been characterized by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), only two and three 1Ax alleles of Glu-A1 m x were detected by Xu et al (2009) and Alvarez et al (2006), respectively.…”
mentioning
confidence: 99%
“…In common wheat, the gene coding the subunit 1Ay is unexpressed because of a premature stop codon (Forde et al 1985) or the insertion of a transposon-like element within its coding region (Harberd et al 1987). However, this subunit is active in many lines of diploid wheat (AA) and the tetraploid wheats T. turgidum (AABB) and T. timopheevii (AAGG) (Ciaffi et al 1991(Ciaffi et al , 1998Ma et al 2007;Jiang et al 2009;Xu et al 2009;Hu et al 2012). Active 1Ay genes have been cloned from the wild diploid wheats T. urartu and T. monococcum ssp.…”
mentioning
confidence: 99%